A DIY Guide to Telemedicine for Clinicians - Bhattacharyya, S.B (Springer Singapore : Imprint: Springer, 2017)
This book is a do-it-yourself guide for clinicians who wish to set up and run a telemedicine facility of their own. The contents are largely based on the understanding and experience gained by the author as a practising physician, management post-graduate (capstone thesis was on telemedicine) and as a business architect for digital health systems over more than thirty years. Full of management techniques, tricks and tips written in an easy-to-follow manner, this book provides sufficient information to clinicians looking to leverage telemedicine to augment their range of service offerings that would lead to increased levels of patient satisfaction. Various aspects related to definitions, technology, infrastructure, methodologies and legal issues for setting up and running telemedicine services have been dealt with to sufficient depths for the readers to help grasp the issues involved. Sections on privacy, confidentiality and data integrity have been provided to help allay the many concerns the readers might have in those regards. Additionally, financial evaluations based on realistic-enough figures have been used to demonstrate that telemedicine is a viable option financially. Although meant primarily for medical doctors, any care provider including institutional will be able to use the contents to plan, design, set up and run telemedicine services that they feel would benefit those who receive their care.
Keywords: Medicine.; Internal medicine.; elektronické knihy; electronic books